2021
DOI: 10.1007/s10340-021-01420-0
|View full text |Cite
|
Sign up to set email alerts
|

Overwintering, cold tolerance and supercooling capacity comparison between Liriomyza sativae and L. trifolii, two invasive leafminers in China

Abstract: Liriomyza sativae Blanchard and Liriomyza trifolii (Burgess) are two highly polyphagous pests that successively invaded China in the 1990s and 2000s, respectively, threatening vegetable and horticultural plants. Competitive displacement of L. sativae by L. trifolii occurred during the expansion process of the latter in southern China. However, whether L. trifolii can expand their range to northern China and, if so, how they compete with L. sativae in northern China remains unclear. Overwintering and cold toler… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
(27 reference statements)
2
5
0
Order By: Relevance
“…Survival of the two species decreased significantly when exposed to a gradient of cold temperatures, and L. trifolii pupae were more cold tolerant than L. sativae pupae. Interestingly, adults of both species exhibited similar levels of cold tolerance; in this respect our results are similar to prior studies where thermal resistance of L. trifolii was stronger than L. sativae [14,43].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Survival of the two species decreased significantly when exposed to a gradient of cold temperatures, and L. trifolii pupae were more cold tolerant than L. sativae pupae. Interestingly, adults of both species exhibited similar levels of cold tolerance; in this respect our results are similar to prior studies where thermal resistance of L. trifolii was stronger than L. sativae [14,43].…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the SCP of L. trifolii was significantly lower than L. sativae. Previous studies also confirmed that the SCP of L. trifolii pupae is much lower than L. sativae, indicating a huge difference in SCPs of the two species [14,26,28]. As described by Bale (1996) [61], there are five classes of insect cold hardness, and based on our survival data and SCP data, L. trifolii is chill susceptible and L. sativae is freeze avoiding.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations